2009
DOI: 10.1111/j.1476-5381.2009.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

The end of a myth: cloning and characterization of the ovine melatonin MT2 receptor

Abstract: Background and purpose: For many years, it was suspected that sheep expressed only one melatonin receptor (closely resembling MT1 from other mammal species). Here we report the cloning of another melatonin receptor, MT2, from sheep. Experimental approach: Using a thermo-resistant reverse transcriptase and polymerase chain reaction primer set homologous to the bovine MT2 mRNA sequence, we have cloned and characterized MT2 receptors from sheep retina. Key results: The ovine MT2 receptor presents 96%, 72% and 67%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 58 publications
(140 reference statements)
3
51
1
1
Order By: Relevance
“…We also found that the basal gene expression of proinflammatory cytokines receptors in the PT was similar during LN and SN. The fact that LPS promotes both TNF receptors gene expression and IL6ST gene expression in LN but not in SN period may result from the different level of melatonin during these two photoperiods, because the PT is exclusive pituitary structure expressing melatonin binding sites (Cogé et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the basal gene expression of proinflammatory cytokines receptors in the PT was similar during LN and SN. The fact that LPS promotes both TNF receptors gene expression and IL6ST gene expression in LN but not in SN period may result from the different level of melatonin during these two photoperiods, because the PT is exclusive pituitary structure expressing melatonin binding sites (Cogé et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We expect the classification of melatonin receptors will continue to evolve as operational and structural data for existing receptors are further defined and possible variants and/or new receptors are characterized. This is the case for the recent cloning of the ovine MT 2 receptor, where for many years it was suspected that sheep possessed only one melatonin receptor (Cogé et al, 2009).…”
Section: International Union Of Basic and Clinical Pharmacology Crmentioning
confidence: 99%
“…Although it is not functional in some seasonal species, MT2 has recently been characterised in the sheep PT, with expression levels lower than those of MT1 [118]. With its ability to form heterodimers with MT1 [117], the involvement of MT2 in melatonin signalling in the PT remains to be investigated.…”
Section: Perspectivesmentioning
confidence: 99%